Circadian Control of Antibacterial Immunity: Findings from Animal Models - Tsoumtsa, Landry L.; Torre, Cedric; Ghigo, Eric (Frontiers in Cellular and Infection Microbiology, 2016)
Most of the biological functions, including the immune system, are linked to circadian rhythms in living organisms. Changes occurring to biological parameters as the result of these circadian rhythms can therefore affect the outcome of a disease. For decades, model organisms have proven to be a great tool to understanding biological mechanisms such as circadian cycle and immunity. In this review, we created an inventory of the use of model organisms in order to decipher the relation between circadian rhythms and antibacterial immunity.